Islam and english: Islamizing our Malaysian youths / Sheema Liza ldris and Zuraidar Badaruddin - ldris, Sheema Liza; Badaruddin, Zuraidar (2006)
Youths nowadays are always associated with degrading moral values like criminal violence (Surett/ 1994). They are involved in many ill-social activities like drugs. crimes or even prostitutions. Thus, as educators we must take this issue seriously because these youths are actually our future. We do not want youths who are involved in such unhealthy activities to be our leaders in the future. Therefore, this paper looks at how this issue could be looked into from the educational point of view. Though it may sound too perfect and unrealistic, it is here for us to consider and think of the various aspects to educate these youths so we can set a good example to the Muslim world.